Cytotoxic and genotoxic profiles of benzo[a]pyrene and N-nitrosodimethylamine demonstrated using DNA repair deficient DT40 cells with metabolic activation. (February 2016) - Ooka, Masato; Takazawa, Hironori; Takeda, Shunichi; Hirota, Kouji
Abstract: Benzo[a]pyrene and N-nitrosodimethylamine are major genotoxic compounds present in cigarette smoke, food and oil. To examine the type(s) of DNA damage induced by these compounds, we used a panel of DNA-repair-pathway-deficient mutants generated from chicken DT40 cells and achieved metabolic activation of the test compounds by including rat liver S9 mix. Consistent with expections, benzo[a]pyrene and N-nitrosodimethylamine require metabolicactivation to become genotoxic. The REV3 −/− mutant cell line exhibited the highest sensitivity, in terms of increased cytotoxicity, to the both compounds after metabolic activation consistent with the known ability of these two compounds to induce DNA adducts. Strikingly, we found that the RAD54 −/− /KU70 −/− cell line, a mutant defective in the repair of double-strand breaks, is sensitive to benzo[a]pyrene, suggesting that this compound also induces strand breaks in these cells. In this study we combined a previously employed method, metabolic activation by S9 mix, with the use of a DNA-repair mutant panel, thereby broadening the range of compounds that can be screened for potential genotoxicity. Graphical abstract: Highlights: BaP and NDMA show genotoxic potentials in DT40 cells only when they are metabolically activated. Translesion DNA synthesis defective REV3 −/− mutant cells exhibit the highest sensitivity to BaP and NDMA. DSB repair defective RAD54 −/−/ KU70 −/− cells also exhibit hypersensitivity to BaP. BaP induces DSBs directly but not as a result of replication fork collapse.